The Effect of Job Stress on the Performance of Employees in the Banking Sector - Jain, Ravvi (Journal of Commerce and Trade, 2021)
Now-a-days stress has become an integral part of jobs in banking sector. Competition is growing day by day thus increasing the levels of stress among employees. An employee spend almost one third of his life on work, and sometimes he has to face a lot of stress during his/her job. The nature of the job has gone through extreme changes over the last decade and it is still changing rapidly. Stress in a workplace has touched almost all professions, starting from executive levels to co-workers who are directly engaged in the production. Employees suffering with stress at work place, try to withdraw themselves from stressors in terms of high turnover and absenteeism from work. Stress has a direct impact on employee performance. Stress leads to improve performance to an optimum point beyond the optimum point further stress and arousal have detrimental effect on performance. Employees who face highly stressful situation constantly for a long period are bound to experience some change in attitude. They develop negative thinking, low morale and job dissatisfaction and fail to maintain friendly interpersonal relation with co-employees. This is because employees who work in highly stressful situations may feel tired and depressed. They also create physical and mental problem such as high blood pressure, hearing problem and mental disorder. Classification-JEL : L51, O14